A dimolybdenum paddlewheel as a building block for heteromultimetallic structures. Issue 5 (10th January 2020) - Knöfel, Nicolai D.; Schoo, Christoph; Seifert, Tim P.; Roesky, Peter W.
Abstract : A series of heteromultimetallic complexes, containing a Mo2 4+ core unit, were synthesized based on a bifunctional phosphine–carboxylic acid ligand system, leading i.e. to the formation of supramolecular structures via aurophilic interactions. Abstract : Diphenylphosphine functionalized propionic acid was applied for the synthesis of heteromultimetallic dimolybdenum(ii ) complexes. The ligand features both carboxylic acid and phosphine functionalities, allowing the selective synthesis of a tetracarboxylate bridged Mo2 (ii )-paddlewheel structure in a first step. Due to the symmetrically arranged phosphine functionalities, the dimolybdenum(ii ) complex was utilized as a metalloligand. Subsequent coordination of late transition metal ions, such as gold(i ), rhodium(i ), iridium(i ) or ruthenium(ii ) to the phosphine moieties allowed the formation of heteromultimetallic structures. The flexibility of the diphenylphosphino propionate ligand system enabled intermolecular aurophilic interactions in the Au(i ) functionalized dimolybdenum(ii ) complexes. Depending on the Au(i ) species applied, either a dimeric structure or a 1D coordination polymer was formed in the solid state. These structures represent the first examples of heterometallic dimolybdenum(ii ) complexes, forming supramolecular structures via aurophilic interactions.